1970
DOI: 10.3126/narj.v6i0.3340
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analyses in Sugarcane

Abstract: This study was conducted to determine the contribution of different traits to cane yield in sugarcane (Saccharum officinarum L). Sixty-five clones were evaluated in a replicated field experiment at Sugarcane Research Programme, Jitpur, Nepal in 2003 for six morphological characters under irrigated conditions. Analysis of variance revealed significant differences for all the characters studied. Cane yield showed positively and highly significant correlation with single cane weight, stalk length and millable can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
2
27
0
Order By: Relevance
“…But the negative association of stalk diameter with stalk count 10 months after planting and millable cane number and its positive significant association with cane yield should be treated with caution. The significant negative association of stalk diameter with millable cane number was reported [1] [17] [29]. Millable cane number was also negatively and significantly correlated with leaf width and leaf area which had positive significant association with cane yield.…”
Section: Correlationmentioning
confidence: 59%
See 2 more Smart Citations
“…But the negative association of stalk diameter with stalk count 10 months after planting and millable cane number and its positive significant association with cane yield should be treated with caution. The significant negative association of stalk diameter with millable cane number was reported [1] [17] [29]. Millable cane number was also negatively and significantly correlated with leaf width and leaf area which had positive significant association with cane yield.…”
Section: Correlationmentioning
confidence: 59%
“…In this case selecting for the character millable cane number would produce maximum yield as compared with any of the other characters. [1] [28] also indicated the importance of millable cane number in selection for higher cane yield. In their study [7] [9], found that cane yield was more closely correlated with stalk population than weight per stalk or stalk diameter.…”
Section: Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…lationship between various characters and also the type and extent of the contribution to yield (Panhwar et al, 2003;Chaudhary and Joshi, 2005). Genotypic and phenotypic correlations were observed between ten characters under four different moisture levels and are presented in Tables 7 to 10, respectively.…”
Section: Genotypic and Phenotypic Correlationmentioning
confidence: 99%
“…Each correlation coefficient between a predictor variable and the response variable is partitioned into its component parts: the direct effect or path coefficient (a standardized partial regression coefficient) for the predictor variable and indirect effects which involve the product of a correlation coefficient between two predictor variables with the appropriate path coefficient in the path diagram (Dewey and Lu, 1959). By determining the interrelationships among seed yield components, a better understanding of both the direct and indirect effects of the specific components can be attained (Chaudhary and Joshi, 2005).…”
Section: Introductionmentioning
confidence: 99%